2015
DOI: 10.1016/j.seizure.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual disability increase sudden unexpected death in epilepsy (SUDEP) risk?

Abstract: Overall we found ID definitions and specified standardized mortality rates and impact of institutionalization to be quite poorly presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…Other studies have reported increased mortality rates among people with intellectual disability and epilepsy, 10 with a particular concern over the contribution of sudden unexpected death associated with epilepsy. 20,21 Mortality among people with Down syndrome has been more widely studied. [22][23][24][25] The findings from these investigations are consistent with the high risk of death we found among people with Down syndrome.…”
Section: Contextmentioning
confidence: 99%
“…Other studies have reported increased mortality rates among people with intellectual disability and epilepsy, 10 with a particular concern over the contribution of sudden unexpected death associated with epilepsy. 20,21 Mortality among people with Down syndrome has been more widely studied. [22][23][24][25] The findings from these investigations are consistent with the high risk of death we found among people with Down syndrome.…”
Section: Contextmentioning
confidence: 99%
“…133,134 A Swedish study 135 of 1478 people with ID found associations between epilepsy and mortality between 1987 and 1992, with an estimated SMR of 5.0 for those with epilepsy compared with 1.6 for those without epilepsy. This compares with the HRs we found of 6.0 and 3.2 before adjusting for mortality (see Table 23).…”
Section: Mortalitymentioning
confidence: 99%
“…Additional risk factors include a history of nocturnal seizures as well as nonmodifiable factors such as earlier-onset epilepsy, male gender, and neurological comorbidities. 17,23,24 There has not been a systematic study of risk factors for SUDEP specific to children. The search for potential SUDEP biomarkers has identified associations with prolonged postictal electroencephalographic suppression and cardiac and respiratory abnormalities in the postictal period.…”
Section: How Common Is Death In Pediatric Epilepsy?mentioning
confidence: 99%